Why Are Elites More Cosmopolitan than Masses? - Oliver Strijbis; Céline Teney; Marc Helbling (The Struggle Over Borders. Cosmopolitanism and Communitarianism, 2019)
Compares cosmopolitan versus communitarian issue positions by mass publics and elites across our study. We investigate whether there is an attitude gap between elites, who tend to adhere to cosmopolitan positions, and mass publics with more communitarian leanings. Contrasting mass opinion surveys with results from our own elite survey, we show that the mass-elite divide on globalization issues is indeed pervasive and found in all five countries of study. We consider both economic causes in the shape of diverging material interests and cultural ones, the latter pointing towards cultural capital and symbolic boundaries defining transnational cosmopolitan class consciousness. The results align more with the cultural than with the economic explanation. Political elites in the five countries display convergent cosmopolitan positions across issues as varied as international trade, climate change, migration and supranational integration. Mass publics are much more divided on these issues. Also, education alone does not explain the mass-elite gap because the elites are still significantly more cosmopolitan than highly educated members of mass publics, even within the same country.
Keywords: 300; cosmopolitanism; elites; public opinion; migration; trade; climate change; supranational integration; representation; cultural capital; class